IDENTITAS DAN KEPENTINGAN DALAM KEBIJAKAN LUAR NEGERI INDONESIA TERHADAP ISU HAK ASASI MANUSIA ETNIS UIGHUR - Angga Nurdin Rachmat (Jurnal Dinamika Global, 2025)
The human rights issues of the Uighur ethnic group have become the international spotlight as a result of the policies implemented by China government which are considered to have violated human rights. For Indonesia, the human rights issue of the Uighur ethnic group is a dilemma in itself that has emerged in foreign policy both at the bilateral level towards China and bilaterally through the UN Human Rights Council mechanism. Indonesia's foreign policy is considered ambiguous because it does not reflect Indonesia's position as a member of the UN Human Rights Council and Islamic solidarity. Therefore, this article attempts to discuss by presenting the question why there is ambiguity in Indonesia's foreign policy in responding to the human rights issue of the Uighur ethnic group? The discussion of this question was analyzed using a constructivist approach through identity and interests with the argument that Indonesia's foreign policy towards human rights issues of the Uighur ethnic group was based on personal and social identities, giving rise to differences in interests that must be achieved. The article was prepared using qualitative methods with secondary data used to support research arguments. This paper finds that the foreign policy presented by Indonesia as an alternative has emerged based on its identity as a developing country with an interest in maintaining and maintaining good relations with China and an identity as a global human rights promoter with an interest in avoiding politicization of the UN Human Rights Council by Western countries.